Impact of Mycobacterium tuberculosis H37Rv Infection on Extracellular Vesicle Cargo in Macrophages: Implications for Host–Pathogen Interaction - Manuel G. Salgado-Cantú; Luis Horacio Gutiérrez-González; Silvia Guzmán-Beltrán; María Teresa Herrera; Carmen Sarabia; Yolanda González (Microorganisms)
Tuberculosis (TB) is one of the most common respiratory infections worldwide, and it is caused by Mycobacterium tuberculosis (Mtb). Mtb employs immune evasion mechanisms that allow the disease to become chronic. Despite extensive research, the host–pathogen interaction remains incompletely understood. Extracellular vesicles (EVs) are small membrane particles that play a regulatory role in infectious diseases. Host-derived EVs have been identified as carriers of proteins, messenger RNA, and lipids from both the host cells and the pathogens. In this study, we assessed the cargo of EVs in human macrophages infected with the virulent strain H37Rv of Mtb at 1 and 24 h post-infection (hpi). The results showed that 1 hpi, infected macrophages secreted EVs containing Mtb proteins (15 to 37 kDa) and Ag85 kDa, as well as RNA transcripts (ESAT-6, 5KST, Ag85, IS6110, 30 kDa, 19 kDa, and MPT64). However, these decreased at 24 hpi. The infection of macrophages with Mtb was observed to result in the release of EVs containing Ag85 protein and RNA transcripts of Mtb; this process appeared to diminish after 24 hpi, suggesting the existence of an evasion mechanism. Both Ag85 and the RNA transcripts could be potential biomarkers for the diagnosis of TB patients.